Local champion’s role in community-based tourism development: a character strengths approach - Abdul, Norzaris; Kler, Balvinder Kaur; Siao, Fui Wong (GADING (Online) Journal for Social Sciences, 2024)
Within the rural tourism literature, successful community-based tourism is often attributed to a „local champion‟. The literature has evaluated such individuals and produced a list of attributes and traits which are deemed necessary. A gap remains in that thus far, the local champion has not been understood through theoretically grounded concepts. This study combines Values in Action-character strengths and Mintzberg‟s managerial roles to produce a new understanding of local champions‟ tenacity in community-based tourism. Using a qualitative research design, a group of twelve, homogenous, purposive sample of „local champions‟ were recruited to attend semi-structured interview sessions. The study setting is Sabah, Malaysian Borneo where government support for rural tourism spans ten years aiming to be a world-class rural tourism destination by 2030. Through a deductive thematic analysis, the study found only twenty-three character strengths were evident in the data, as were the interpersonal, informational and decisional roles in the lived experience of local champions. Implications for capacity building and well-being are discussed as well as future work. As community-based tourism prospers, local champions will remain relevant for rural tourism and the need to train the next generation will need careful consideration. The character strengths approach proposed in this study is one way to do so.